1979
DOI: 10.1021/jf60225a017
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of the experimental aquatic herbicide fluridone from lakes and ponds

Abstract: The dissipation of the aquatic herbicide fluridone, l-methyl-3-phenyl-5-[3-trifluoromethyl)phenyl]-4(lJ/)-pyridinone, has been determined in experiments conducted in small ponds at three different geographic regions in the United States and in Gatun Lake of the Panama Canal. Fluridone dissipated rapidly from the water, with a half-life averaging 5 days. The dissipation was due in part to deposition on hydrosoil and uptake by aquatic plants, although evidence is presented to suggest photolysis as a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 1 publication
1
17
0
3
Order By: Relevance
“…It has also been tested for weed control in cotton (Webster et al, 1977). Studies on the disappearance of fluridone in aquatic systems have indicated that it has an average half-life of about 5 days in pond and lake waters (West et al, 1979;Muir et al, 1980). Dissipation of the herbicide in sediments and terrestrial soils under field conditions has been reported to be much slower than in water.…”
Section: Fluridone [L-methyl-3-phenyl-5-[3-(trifluoromethyl)-mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been tested for weed control in cotton (Webster et al, 1977). Studies on the disappearance of fluridone in aquatic systems have indicated that it has an average half-life of about 5 days in pond and lake waters (West et al, 1979;Muir et al, 1980). Dissipation of the herbicide in sediments and terrestrial soils under field conditions has been reported to be much slower than in water.…”
Section: Fluridone [L-methyl-3-phenyl-5-[3-(trifluoromethyl)-mentioning
confidence: 99%
“…Dissipation of the herbicide in sediments and terrestrial soils under field conditions has been reported to be much slower than in water. In sediments half-lives ranging from about 3 month to greater than 12 months have been observed (West et al, 1979;Muir et al, 1980). In sediments half-lives ranging from about 3 month to greater than 12 months have been observed (West et al, 1979;Muir et al, 1980).…”
Section: Fluridone [L-methyl-3-phenyl-5-[3-(trifluoromethyl)-mentioning
confidence: 99%
“…As percentagens médias de recuperação foram de 71% para 100 µg kg -1 , 73% para 200 µg kg -1 , 65% para 400 µg kg -1 e 60% para 2.000 µg kg -1 . West (1978) e West et al (1979) obtiveram valores médios de recuperação maiores (89 e 87%, respectivamente), mas as variações das percentagens de recuperação em função das concentrações foram muito maiores nestes trabalhos (Tabela 1). As percentagens de recuperação obtidas no método desenvolvido são adequadas para matrizes complexas, que requerem diversas etapas de limpeza e purificação do extrato para extração do analito.…”
Section: Resultsunclassified
“…As etapas de limpeza de amostras e a utilização de colunas de florisil e cromatografia líquida com detector de UV visível também mostraram-se eficientes e de fácil execução, descontando-se a não-necessidade de derivatização do herbicida, fundamental para que o herbicida seja analisado por cromatografia gasosa (West, 1978;West et al, 1979).…”
Section: Resultsunclassified
See 1 more Smart Citation